2006
DOI: 10.1007/s00418-006-0255-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of phospho-S6 kinases: a new way to detect mitosis in tissue sections and in cell culture

Abstract: During a study on the mTor pathway in the rat kidney we observed a striking increase of the phosphorylation of the S6 kinase in mitosis. In cryostat sections of perfusion-Wxed tissue mitotic cells appeared as bright spots in immunoXuorescence using an antibody speciWc for the phosphorylation site Thr421/Ser424. They were easily spotted in overviews with the objective 4£ and 10£. ImmunoXuorescence was weak during the interphase. During the prophase it increased in both the nucleus and the cytoplasm and it remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…[26][27][28][29] Phosphorylation at Thr421/Ser424 of p70S6K1, a downstream effector of mTOR, is also strongly upregulated during mitosis, and the S6 kinase p54S6K2 has been identified as a centrosome-located kinase throughout the cell cycle. [30][31][32] Our current findings confirm that mTOR Ser2481 autophosphorylation, a recently described pharmacodynamic biomarker that directly monitors the effects of rapamycin on the assembly and function of mTORC complexes, should be added to the growing list of phospho-active forms of proteins of the AMPK/mTOR/S6K1 signaling axis that reside at the mitotic and cytokinetic apparatus.…”
Section: Anti-phospho-mtorsupporting
confidence: 77%
“…[26][27][28][29] Phosphorylation at Thr421/Ser424 of p70S6K1, a downstream effector of mTOR, is also strongly upregulated during mitosis, and the S6 kinase p54S6K2 has been identified as a centrosome-located kinase throughout the cell cycle. [30][31][32] Our current findings confirm that mTOR Ser2481 autophosphorylation, a recently described pharmacodynamic biomarker that directly monitors the effects of rapamycin on the assembly and function of mTORC complexes, should be added to the growing list of phospho-active forms of proteins of the AMPK/mTOR/S6K1 signaling axis that reside at the mitotic and cytokinetic apparatus.…”
Section: Anti-phospho-mtorsupporting
confidence: 77%
“…Although we did observe small foci of p-S6K-positive cells (Fig. 3B, inset), this seems to be secondary to focal increases in mitotic rate because S6K is phosphorylated during mitosis (23) and p-S6K is also a welldocumented marker of mitotic cells (24). We also did not observe significant alterations in the patterns or levels of phosphorylation of other putative mTOR substrates including p-4EBP1(Thr 70 ) or p-Akt(Ser 473 ) (data not shown).…”
Section: Female Lkb1mentioning
confidence: 80%
“…Shah et al (27) demonstrated that phosphorylation of those residues (featured by the Thr-421/ Ser-424 site) during mitosis pursued by Cdk1 inactivates S6K1 to terminate protein synthesis prior to cell division (28). A recent report by Schmidt et al (29) demonstrating that phosphorylation of Thr-421/Ser-424 is specifically increased during the G 2 /M phase may also support the finding, whereas during the G 1 phase, there is consensus that the phosphorylation at the autoinhibitory domain is requisite for S6K1 activation (26), as also recently demonstrated by Hou et al (30), where the Cdk5 phosphorylates the Ser-411 site, leading to activation of S6K1. In contrast to such inhibitory regulation of S6K1 during mitosis, however, a recent report by Boyer et al (31) sharply demonstrated that the activity of S6K1 peaks at mitosis, suggesting that S6K1 may also have some roles during the mitotic phase.…”
mentioning
confidence: 99%